2020
DOI: 10.1101/2020.06.05.134445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abiotic treatment to common bean plants results in an altered endophytic seed microbiome

Abstract: 12We performed a pilot study in a controlled growth chamber to investigate how the seed microbiome of 13 the common bean (Phaseolus vulgaris L. (var. Redhawk)) was altered under abiotic treatments relevant 14 for crop management with changing climate. Bean plants were subjected to one of three treatments: 1566% water withholding to simulate mild drought, 50 % Hoagland nutrient solution to simulate 16 fertilization, or control with sufficient water and baseline nutrition. We performed 16S rRNA gene 17 amplicon … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 83 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…As is true for other plant compartments, different plant species or divergent crop lines/varieties/cultivars often have different seed microbiome composition or structure (Wassermann et al 2019; Klaedtke et al 2016; Johnston-Monje and Raizada 2011; López-López et al 2010). However, many seed microbiome studies have reported generally high variability across seed samples from the same plant type and treatment (Bergna et al 2018; López-López et al 2010; Bintarti et al 2020), with strong explanatory value of either seed origin/seed lot, geographic region or soil edaphic conditions (Chartrel et al 2021; Klaedtke et al 2016; Johnston-Monje and Raizada 2011; but see also Adam et al 2018 for an exception). While these insights may call into question the proportion of “inherited” versus acquired seed microbiome members, the high microbiome variability may be in part due to methods applied to extract the microbial DNA from the seed compartment, and different methods applied across studies.…”
Section: Introductionmentioning
confidence: 99%
“…As is true for other plant compartments, different plant species or divergent crop lines/varieties/cultivars often have different seed microbiome composition or structure (Wassermann et al 2019; Klaedtke et al 2016; Johnston-Monje and Raizada 2011; López-López et al 2010). However, many seed microbiome studies have reported generally high variability across seed samples from the same plant type and treatment (Bergna et al 2018; López-López et al 2010; Bintarti et al 2020), with strong explanatory value of either seed origin/seed lot, geographic region or soil edaphic conditions (Chartrel et al 2021; Klaedtke et al 2016; Johnston-Monje and Raizada 2011; but see also Adam et al 2018 for an exception). While these insights may call into question the proportion of “inherited” versus acquired seed microbiome members, the high microbiome variability may be in part due to methods applied to extract the microbial DNA from the seed compartment, and different methods applied across studies.…”
Section: Introductionmentioning
confidence: 99%